Seroprevalence and molecular detection of infectious laryngotracheitis virus (ILTV) in commercial chicken in Gazipur district of Bangladesh (Annals of Bangladesh Agriculture, 2024)
Infectious laryngotracheitis (ILT) is one of the major diseases of chickens that cause great economic losses in commercial chicken farms. It is caused by the infectious laryngotracheitis virus (ILTV). This research work was designed to investigate the seroprevalence of ILTV in commercial chicken farms in Gazipur district. A total of 590 blood sera were collected randomly from commercial chicken farms from different locations in Gazipur district. An antigen-coated indirect ELISA was performed to determine the antibody titer against ILTV in these sera. Moreover, gross and histopathological changes in different organs were investigated. Polymerase chain reaction (PCR), a molecular detection method, was performed to detect the fragment of the glycoprotein ‘C’ (gC) gene of ILTV in the infected chicken. Overall, 195 out of 590 serum samples were positive for anti-ILTV IgG, representing 33.05% of positive cases. The highest mean titer of ILTV antibody was found in anti-ILTV-vaccinated layer chickens with a mean titer of 3554. In seasonal variation, the highest prevalence of ILTV was recorded during the winter, followed by the rainy and summer seasons. The prevalence of ILTV was the highest at the age of 10-30 weeks in layer chickens. Necropsy findings of dead chickens showed severe congestion and fibrosis in the lungs and trachea, with occlusion of the tracheal lumen by mucus, caseous exudates and blood. Microscopically, hemorrhage and huge infiltrations of inflammatory cells were found in trachea and lungs. Moreover, the nucleotide sequence of ‘gC’ gene of ILTV was amplified successfully and yielded 1.26 kbp amplicons. This study suggested that ILTV was endemic in Gazipur district and the PCR technique is a useful molecular tool for diagnosis of ILTV in the commercial chicken industry.Ann. Bangladesh Agric. (2023) 27 (1): 121-135